L-Arginine Supplementation in Type II Diabetic Rats Preserves Renal Function and Improves Insulin Sensitivity by Altering the Nitric Oxide Pathway. (22nd December 2013) - Claybaugh, Taylor; Decker, Sarah; McCall, Kelly; Slyvka, Yuriy; Steimle, Jerrod; Wood, Aaron; Schaefer, Megan; Thuma, Jean; Inman, Sharon
Abstract : Rat studies demonstrated that type II diabetes mellitus (T2DM) decreases both the production and bioavailability of nitric oxide (NO). L-arginine (LA) provides the precursor for the production of NO. We hypothesized that LA dietary supplementation will preserve NO production via endothelial nitric oxide synthase (eNOS) causing renal microvascular vasodilation and increased glomerular blood flow and thus increasing glomerular filtration rate (GFR). This would impede the formation of reactive oxygen species which contributes to cell damage and death. LA supplementation preserved GFR in the treated diabetic rats compared to untreated diabetic rats. We provide evidence that this effect may be due to increased levels of eNOS and urinary cyclic guanosine monophosphate, which leads to renal microvascular vasodilation. Plasma nitrotyrosine was decreased in the LA treated rats; however, plasma nitrite levels remained unaffected as expected. Marked improvements in glucose tolerance were also observed in the LA treated diabetic rats. These results demonstrate that LA supplementation preserves NO activity and may delay the onset of insulin resistance and renal dysfunction during hyperglycemic stress. These results suggest the importance of the NO pathway in consequent renal dysfunction and in the development of insulin resistance in diabetic rats.